Um estudo exploratório da construção de saberes docentes provenientes de interações discursivas no estágio curricular - Claudia Marcia da Silva Ferreira (2009)
This work consists of exploring the discursive interactions experienced by future Mathematics teachers in their supervised traineeship, based in terms of knowledge construction. An empiric research was accomplished in an urban public school of Belo Horizonte, Brazil. Threemoments of discursive interaction were considered: the trainees and a teacher of two Junior School classes; the trainees and the students of theses classes and, the trainees and the researcher. This is a qualitative research, characterized by participant observation based in theethnographic research. We used three instruments to collect data: (a) audio and video recordings of classroom observation; (b) audio recordings of interviews with the trainees; (c) a journal with written reports. This research results show that the supervised traineeship,though as a familiarization with the workplace atmosphere (the classroom), give opportunities to trainees make deep reflections about methodological strategies to teach the subject, as well as to mobilize and produce fundamental knowledge to the professional development of these future teachers. Final considerations can be outlined regarding development, pedagogical implications and results of this study. Some suggestions can be mentioned: the supervisor must creates moments where the trainees can question themselves about their actions,contradictions and conceptions and, create opportunities for discussion, experiences exchange, dialogue between the trainees and the teachers.